The Role of Curriculum, Instruction, and Education Funding in Improving the Quality of Basic Education (Case Study: SDN 14 Rantau Selatan) - Tamrin Harahap; Amin Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The quality of basic education is the primary foundation for the development of highquality human resources. This study aims to analyze the roles of the curriculum, teaching and learning, and educational funding in improving the quality of basic education at SDN 14 Rantau Selatan, Rantau Selatan Subdistrict, Labuhan Batu Regency, North Sumatra Province. The research method used was qualitative descriptive through field studies, in-depth interviews with the principal and teachers, as well as a review of school documents. The results of the study indicate that: (1) the implementation of the Merdeka Curriculum at SDN 14 Rantau Selatan is proceeding gradually with adjustments to the socio-economic characteristics of the plantation community; (2) a contextual learning approach based on local potential has proven to enhance student motivation and understanding; and (3) transparent and accountable management of the School Operational Assistance Fund (BOS) significantly contributes to meeting the school’s operational needs